Second malignant neoplasm in a treated Ewing sarcoma patient: A case report - Mudra, Kakoti Lopa; Zachariya, Choudhury; Jagannath, Sharma (Indian Journal of Child Health, 2018)
Ewing sarcoma (ES) is an aggressive tumor commonly seen in children and young adults. Late effects of ES therapy include the second cancers, a tragic outcome for survivors of such young age. We report a case of a 3-year-old male child who presented with a right maxillary mass extending to the orbit. Fine-needle aspiration cytology and tru-cut biopsy showed features suggestive of a small round cell tumor. Immunohistochemistry confirmed the diagnosis of ES/primitive neuroectodermal tumor. The patient was started on non-metastatic Ewing family tumor protocol with intensity-modulated radiotherapy and responded well to therapy. He was followed up regularly, but after 5 months of initial diagnosis, his peripheral blood smear showed atypical cells resembling blasts. His bone marrow aspiration (BMA) and biopsy showed marrow infiltrated by hematolymphoid malignancy. Based on the positivity of the blasts for myeloperoxidase and non-specific enolase in cytochemistry on the BMA and flow cytometric analysis, a diagnosis of acute myeloid leukemia with monocytoid differentiation was made. We report this case to emphasize the role of the pathologist in differentiating the second malignancies from recurrence of the first malignancy or therapy-related changes, especially in the case of an equivocal morphological picture.